Dari UIA ke ISA : perjalanan dakwah 1 - Badrulamin Bahron (Kepong, Kuala Lumpur : Hubb Marketing (M), 2002)
Author's account of his study in Universiti Islam Antarabangsa and his arrest as political detainee under the Malaysian Internal Security Act.
In Malay.
Koleksi Sumbangan: Dr. Syed Husin Ali.
Keywords: Badrulamin Bahron -- 1961- -- Biography; Politicians -- Malaysia -- Biography; Political prisoners -- Malaysia -- Biography; Malaysia -- Politics and government